Assessment of Availability of Essential Human Resource for Health for EmONC Services in Public Sector of Pakistan (Medical Forum Monthly, 2024)
Objective: To assess availability and establish the current situation of essential human resource shortage for provision of emergency obstetric and new born care in public sector health facilities. Study Design: Observational / descriptive / cross sectional study. Place and Duration of Study: This study was conducted at the Department of Public Health, Contech School of Public Health, Lahore from January 2013 to December 2013.Materials and Methods: A robust surveys were conducted by stratified sampling technique by taking 100% samples. 20% sample of basic health units was taken to assess the availability of essential human resource for health to meet the progress of Millennium Development Goal 4 and 5.Results: Situation of availability of essential human resources at district and tehsil level for provision of maternal and newborn health services was found only 33% at district head quarter hospitals and 3% at tehsil headquarter hospitals. This is an escorting cause of not reducing maternal and child mortality as per target.ConclusionStudy results suggest accelerated provision of essential human resource for health to provide emergency obstetric and new born care to reducematernal and neonatal mortality in the country.